The Role of G-protein Coupled Receptor Proteolytic Site (GPS) Cleavage in Polycystin-1 Biogenesis, Trafficking and Function (Exon Publications, 2015)
Polycystin-1 (PC1) is encoded by PKD1, the principal gene mutated in autosomal dominant polycystic kidney disease (ADPKD). The protein regulates terminal differentiation of tubular structures in the kidney and is required to maintain their structural integrity. A fundamental property of PC1 is post-translational modification by cis-autoproteolytic cleavage at the G-protein coupled receptor proteolytic site (GPS) motif located at the base of the extracellular ectodomain. Defective cleavage likely plays a significant role in the pathogenesis of ADPKD. In mouse models, GPS cleavage of PC1 is essential for the integrity of the distal nephron segments during the postnatal period. While the exact cellular and biochemical functions of PC1 have yet to be fully elucidated, its trafficking and function must be precisely regulated at the subcellular level to ensure proper structure and function of the kidney. Recent evidence shows that GPS cleavage plays a central role in PC1 biogenesis, trafficking and function in vivo. GPS cleavage results in the N-terminal fragment (PC1NTF) and C-terminal fragment (PC1CTF), which remain non-covalently associated to form a heterodimeric PC1 molecule. Cleavage is required for ciliary trafficking of PC1, which occurs in a two-step mechanism. First, PC1 interacts with polycystin-2 (PC2) in the ER and binds Rabep1. PC1/2 complex formation is required for transition of PC1 to the trans-Golgi compartment. Second, once arriving at the trans-Golgi, PC1/2-bound Rabep1 recruits GGA1 and the small GTPase Arl3 sequentially for ciliary targeting. In the absence of cleavage, the PC1/2 complex cannot reach the trans-Golgi. This article will discuss the roles of GPS cleavage for PC1 structure, trafficking and function that are relevant for normal activity of polycystin-1 and in cystogenesis of ADPKD.